A taxonomic review of Lampris guttatus (Brünnich 1788) Lampridiformes; Lampridae) with descriptions of three new species - Underkoffler, Karen E.; Luers, Meagan A.; Hyde, John R.; Craig, Matthew T. (Zootaxa, 2018)
The genus Lampris (Lampridae) currently comprises two species, Lampris guttatus (Brünnich 1788) and L. immaculatus (Gilchrist 1905) commonly known as Opah and Southern Opah, respectively. Hyde et al. (2014) presented DNA sequence data which revealed the presence of five distinct, monophyletic lineages within L. guttatus. In this paper, we present morphological and meristic data supporting the presence of five species previously subsumed within L. guttatus (Brünnich 1788). We restrict Lampris guttatus (Brünnich 1788), resurrect L. lauta (Lowe 1838), and describe three new species of Lampris. A key to the species of Lampris is provided.